Neuro4PD: An Initial Neurorobotics Model of Parkinson's Disease - Pimentel, Jhielson M.; Moioli, Renan C.; de Araujo, Mariana F. P.; Ranieri, Caetano M.; Romero, Roseli A. F.; Broz, Frank; Vargas, Patricia A. (Frontiers in Neurorobotics, 2021)
In this work, we present the first steps towards the creation of a new neurorobotics model of Parkinson’s Disease (PD) that embeds, for the first time in a real robot, a well-established computational model of PD. PD mostly affects the modulation of movement in humans. The number of people suffering from this neurodegenerative disease is set to double in the next 15 years and there is still no cure. With our new model, we were capable to further explore the dynamics of the disease and investigate the emergence of the tremor motor symptom using a humanoid robot. Results show that the embedded model was capable of fairly reproducing this symptom during the performance of a simple behavioural task. We believe that this work characterises an important step towards the creation of a new neurorobotics model of PD that could test and inform new therapies and help to reduce and replace animals in research.